Autoantibodies to apolipoprotein A-I in hepatitis C virus infection: a role in disease progression? - Bridge, Simon H.; Pagano, Sabrina; Lodge, John K.; Shawa, Isaac T.; Marin-Crespo, Paula; Cramp, Matthew E.; Sheridan, David A.; Taylor-Robinson, Simon D.; Vuilleumier, Nicolas; Neely, R. Dermot G.; Bassendine, Margaret F. (Frontiers in Immunology, 2025)
BackgroundChronic HCV (CHC) infection is associated with autoimmunity. IgG autoantibodies to apolipoprotein A-I (AAA-I) predict all-cause mortality. We evaluated AAA-I in CHC patients and in those who were not viraemic, either because of spontaneous resolution (SR) of infection or HCV clearance following sustained virological response (SVR) after interferon therapy. We limited the study to HCV genotypes 1 and 3, the dominant HCV genotypes circulating in the UK.MethodsSerum samples from 126 CHC patients and 114 nonviraemic individuals (25 SR and 89 SVR) were assayed for AAA-I and lipoproteins. AUC was calculated for AAA-I and HDL-related parameters and used to predict cirrhosis. Fibronectin (FN) and FN-mRNA were measured in human hepatic stellate cells (LX-2) in the presence or absence of AAA-I.ResultsAAA-I was found in 47% of patients with CHC, 37% of SVR patients, and 16% of SR individuals (CHC vs. SR, p = 0.004). AAA-I levels in CHC patients were higher in those with cirrhosis (p = 0.0003). The AUC for AAA-I, apoA-I, and HDL-C in predicting cirrhosis was 0.72 (p < 0.001), 0.65 (p = 0.01), and 0.64 (p = 0.02). After 48 h in the presence of AAA-I, LX-2 cells showed an 80% increase in FN-mRNA compared to the LX-2/IgG control (p = 0.028) and higher levels of FN (p = 0.0016).ConclusionsCHC is often associated with AAA-I, and these can persist after SVR. AAA-I is a robust predictor of cirrhosis in CHC infection. LX-2 cells exposed to AAA-I showed increased FN. Further studies are warranted to define the role of AAA-I in promoting not only viral persistence but also fibrosis.